Effectiveness of PTechSIA questionnaire in quantifying phacoemulsification surgical technique variations: a pilot study - Marzuki, Nazaryna; Md Mustafa, Md Muziman Syah; Ab. Halim, Noorhazayti; Mohd. Kamal, Khairidzan; Yusof, Firdaus; Hilmi, Mohd Radzi; Ahmad, Norsham; Abd Rahman, Mohd Harimi; Akhtar Ali, Ahmad Nurfahmi (2020)
Introduction: Detailed-documentation of phacoemulsification surgical techniques in operative note is not a routine in clinical practice. However, this information is crucial in order to quantify the variations in surgeon’s surgical technique and to further evaluate the surgeon’s surgically induced astigmatism (SIA) predictability. Aim: To assess the effectiveness of Phacoemulsification Technique Related to Surgically Induced Astigmatism (PTechSIA) questionnaire in quantifying the phacoemulsification surgical technique variations. Methods: Four ophthalmic surgeons (Surgeons A, B, C and D) at IIUM Eye Specialist Clinic were involved in this study. A validated self-administered questionnaire with 9 items (PTechSIA, patency number: LY2018002935) was employed to assess the surgeons’ surgical techniques during phacoemulsification. All the responds were scored for each item using Variation Score (VS). Score ‘0’ was given, when a surgeon ticked only one option of the surgical techniques, Score ‘1’ when a surgeon ticked two options, and so on for each item. VSs of all 9 items were summed up to obtain Total Variation Score (TVS). A higher TVS indicated a higher variation in surgical techniques. Results: PTechSIA showed that all surgeons had different TVS. Surgeons A and B had TVS of 1, whereas Surgeons C and D had TVS of 0 and 3, respectively. TVS of each surgeon indicated that all surgeons had variations in phacoemulsification surgical techniques. Conclusions: PTechSIA is an effective tool to evaluate and quantify the variation of surgeons’ surgical techniques in phacoemulsification. Hence, PTechSIA is suggested to be used extensively for a larger scale of surgeons in future research related to phacoemulsification surgical technique and SIA.